The efficacy of sentinel lymph node mapping with indocyanine green in cervical cancer - Ju-Hyun Kim (World Journal of Surgical Oncology, 2018)
Abstract Background Lymph node metastasis is a significant predictive factor for disease recurrence and survival in cervical cancer patients. Given the importance of lymph node metastasis, it is imperative that patients harboring metastasis are identified and can undergo appropriate treatment. Sentinel lymph node (SLN) mapping has drawn attention as a lymph node mapping technique. We evaluated the feasibility and efficacy of (SLN) mapping using indocyanine green (ICG) in cervical cancer. Methods We performed a single-center, retrospective study of 103 surgically treated cervical cancer patients who underwent SLN mapping. After using ICG to detect SLN during surgery, we removed the SLNs followed by laparoscopic or robotic-assisted radical surgery and bilateral pelvic lymphadenectomy. Results Stage IB1 was the most common (61.17%). At least one SLN was detected in all cases. Eighty-eight patients (85.44%) had bilateral pelvic SLNs. The mean number of SLN per patient was 2.34. The side-specific sensitivity was 71.43%, the specificity was 100%, the negative predictive value (NPV) was 93.98%, and the false negative rate (FNR) was 28.57%. In cases of tumors smaller than 2 cm with negative lymph node metastasis on imaging, the study revealed a side-specific sensitivity of 100%, a specificity of 100%, a NPV of 100%, and a FNR of 0%. Large tumor size (≥ 4 cm), a previous history of a loop electrosurgical excision procedure (LEEP), depth of invasion (≥ 50%), the microscopic parametrial (PM) invasion, and vaginal extension were significantly associated with the false-negative detection of SLN. Moreover, the microscopic PM invasion was the only risk factor of the false-negative detection of SLN in multivariate analysis. Conclusion SLN mapping with ICG in cervical cancer is feasible and has high detection rate. The sensitivity of 100% was high enough to perform SLN biopsy alone in an early stage in which the tumor is less than 2 cm, with no lymphadenopathy on image examination. However, for large or invasive tumors, we would have to be cautious about performing SLN biopsy alone. Trial registration Retrospectively registered 2017-0600.